Impact of Homeoprophylactic Arsenicum album 30c on COVID-19 Vaccine-related Adverse Events: A Combined Retrospective–Prospective Cohort Study - Nayak, Debadatta; Bhalla, Ruchika; Kaur, Lovepreet; Bansal, Divya; Singh, Smita; Bagdi, Navita; Michael, James; Chaudhuri, Abhishek; Tyagi, Lalit; Makhija, Bhavna; Madaan, Shikha; Das, Deblina; Shukla, Indu; Sanyal, Srimonti; Saleem, Khan Sheeba; Yadav, Ajay (Homeopathy, 2025)
Objective Arsenicum album 30C (AA30) was recommended by the Government of India for the prevention of coronavirus infection. In the wake of the reporting of COVID-19 vaccine-related adverse events (AEs) and consequent vaccine hesitancy, this study was undertaken to assess the impact of homeo-prophylactic AA30 on COVID-19 vaccine-related AEs.Methods This was a combined retrospective–prospective cohort study that included participants who had been enrolled in an ongoing prospective, parallel cohort study being conducted in urban slums of New Delhi and who had received either or both doses of the COVID-19 vaccine. The reporting of COVID-19 vaccine-related AEs was compared between a cohort that had been receiving homeopathic AA30 as a prophylactic for influenza-like/COVID-like illness with one in which no homeopathic intervention was provided.Results A total of 1,737 participants who received either or both doses of vaccination for COVID-19 were included in the study, out of whom 436 participants were from the medicine cohort (MC) and 1,301 were from the control cohort (CC). Overall odds of developing AEs after either dose of COVID-19 vaccine in MC as compared with CC was found to be statistically significantly lower (overall crude OR = 0.29, 95% confidence interval [CI] = 0.23 to 0.37; p = 0.0001). The adjusted OR after accounting for age, sex, co-morbidities and vaccine type was 0.30 (95% CI = 0.24 to 0.39; p = 0.0001). The protective effect of the medicine against post-vaccination AEs was evident after the first dose as well as after the second dose, with overall crude OR being 0.37 (95% CI = 0.29 to 0.48; p = 0.0001) and 0.28 (95% CI = 0.19 to 0.41; p = 0.0001) respectively.Conclusion Prior use of the homeopathic medicine AA30 was able to significantly reduce COVID-19 vaccine-related AEs.
Keywords: adverse event; Arsenicum album; COVID-19; homeopathy; vaccination